ÐŸÐÐž-1500 Ð¸Ð½Ð³Ð¸Ð±Ð¸Ñ€ÑƒÐµÑ‚ Ð¡Ð°2+-ÐÐ¢Ð Ð°Ð·Ñƒ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Zemlyanskikh, N. G.; Nikolchenko, A. Yu.; Babijchuk, L. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Human erythrocyte Ca2+-ATPase provides the maintenance and regulation of intercellular calcium level. Change in its functional activity under cryopreservation plays an important role in cell survival and structural integrity preservation. PEO-1500 exocellular cryoprotectant inhibits erythrocyte Ca2+-ATPase activity at incubation stage but the following freeze-thawing cycle (â€“196...37Â°C) in its presence does not affect the settled regimen of this enzyme functioning. The inhibition caused by PEO-1500 effect has a reversible character and the erythrocyte Ca2+-ATPase activity is recovered after its dilution in cell suspension that is essential for cryopreserved cell normal functioning in blood bed after transfusion. The inhibition of Ca2+-ATPase activity is apparently associated to physical and chemical membrane modification under this compound effect.